DESAIN DAN PENERAPAN PRESENTASI NARATIF DAN INTERAKTIF OLEH GURU MTS NURUL HUDA SEDATI UNTUK PEMBELAJARAN ABAD KE-21 - Atmaja, Pratama Wirya; Al Haromainy, Muhammad Muharrom; Purnomo, Ryan (Jurnal Abdi Insani, 2024)
The complexity of the 21st century demands an active, interactive, and immersive approach to education. Madrasah Tsanawiyah Nurul Huda Sedati (MTs Nuhati) strongly desires to facilitate such a learning process. To support this mission, we held a two-day training session for applying interactive digital narrative (IDN) media for multimodal, affective, and interactive learning at MTs Nuhati. The first day of the training session provided teachers with skills to design an educational IDN as an MS PowerPoint presentation, while the second day was a simulation of the in-class implementation of the teachers’ presentations. To support the teachers’s comprehension, we delivered a tutorial on educational IDNs based on their literature and also provided an interactive narrative design form, an interactive and narrative MS PowerPoint template, and an example of the template’s application to deliver a specific lesson. Quantitative data from questionnaires and qualitative data from a discussion and our observation prove that the training session has been successful, not only in building skills for creating and implementing educational INDs but also in motivating the teachers to keep learning about educational technology.